Plasma kinetics in a nanosecond pulsed filamentary discharge sustained in Ar–H2O and H2O. (16th November 2018) - Luo, Yuchen; Lietz, Amanda M; Yatom, Shurik; Kushner, Mark J; Bruggeman, Peter J
Abstract: The plasma kinetics of Ar–H2 O and H2 O at atmospheric pressure are of interest for applications in biotechnology where rare-gas plasma jets treat liquid surfaces and in water treatment where discharges are generated in bubbles or directly in liquid water. Due to evaporation resulting from heat transfer to the liquid, for many conditions the mole fraction of water in the plasma can be large—approaching nearly pure water. In this paper, results are discussed from a combined experimental and computational investigation of the chemical kinetics in a high electron density plasma filament sustained in Ar–H2 O at atmospheric pressure. The chemical kinetics were simulated using a 0D global model, validated by measurements of the absolute OH and H densities by laser induced fluorescence (LIF) and two-photon absorption LIF. The primary sources of H and OH during the discharge pulse are dissociative excitation transfer from metastable Ar atoms and Ar dimer excimers at low water concentration and electron impact dissociation of H2 O at high water concentration. In spite of their similar sources, the density of OH was measured to be two orders of magnitude smaller than that of H at power densities on the order of 10 5 Jm −3 . This disparity is due to electron impact dissociation of OH during the discharge pulse and rapid reactions of OH in the presence of high H and O densities in the afterglow. It is often assumed that OH is the dominant non-selective reactive species in water-containing plasmas. These results reinforce the importance of atomic species such as H and O in water containing high energy density plasmas. A numerical parametric study revealed that the lowest energy cost for H2 O2 production is achieved at low energy densities in pure water. The high concentration of atomic radicals, which rapidly recombine, results in an overall lower energy efficiency of reactive species production. In particular, the selectivity of H2 O2 production decreases with increasing power density which instead favors H2 and O2 production.